(untitled) (ARQUISUR Revista, 2017)
In cities nowadays the presence or absence of green spaces for recreation influences the quality of life of residents and the sustainability of it. Numerous studies describe the social, economic, and environmental benefits that recreational areas produce, emphasizing on the importance of their use for the health of city inhabitants. Despite the extensive amount of literature available, it is hard to find unanimity regarding the radii of influence of the different types of recreational public spaces. This study aims to analyze and understand the habits of the inhabitants of the Metropolitan Area of Mendoza (MAM) to determine if the city has enough green spaces and if their distribution satisfies the needs of all its citizens.